POLICE REFORM AS SYSTEM JUSTIFICATION. - FIELDS, SHAWN E. (Journal of Criminal Law & Criminology)
System Justification Theory (SJT) provides a useful lens through which to critique recent police reform efforts. SJT posits that members of society tend to justify and maintain existing social and political systems even when those systems disadvantage them, because the predictability of the status quo provides palliative, epistemic, and existential comfort in what otherwise appears to be an unjust and inequitable societal structure. Contrary to "false consciousness" theories, SJT claims that disadvantaged groups may intentionally rationalize what they know to be an unfair status quo, because doing so reduces social anxiety and threat while providing much desired order and meaning to structurally or systemically broken systems. One such broken system--the American policing machine--continues to enjoy broad system justifying supportfrom advantaged and disadvantaged groups alike, despite incontrovertible evidence of the system's unfairness, ineffectiveness, and inefficiency. This contention may seem at odds with the fact that policing also receives among the most vocal and sustained criticism and calls for change of any stable political structure in the country. But it is those very "reforms" championed and implemented in recent years that proves the inherent desire to defend and maintain the status quo. This Article provides two novel contributions to legal literature. First, it provides the first SJT-specific critique of policing and its ability to maintain itself, relatively unchanged, despite its long history of racialized violence and class exploitation. Second, it utilizes the SJT framework to explore how purported reforms to the policing status quo are designed to defend that status quo as fundamentally sound andfair. The two most heavily funded and implemented policing reforms since the Summer 2020 uprisings against police violence--procedural justice and predictive policing--serve not to transform the structure of policing by eliminating it or reducing its bias and exploitation, but to justify its inherent authority through the façade of objectivity. These reforms provide a veneer of legitimacy, making it easier to rationalize the unchanged and unjust status quo. At root, SJT reveals that defenses ofpolicing rarely derive from logic or facts, but from deep-seated psychological needs to perceive the world as orderly, safe, and fair. Recognizing these motivations is key to fostering productive dialogue about true transformative change.